Analisis Pergerakan Indeks Saham Sektor Pertambangan di Bursa Efek Indonesia - Yulinda Tri Komalasari (Universitas Peradaban, 2019)
The purpose of this study is to analyze the influence of exchange rates, gold prices, and crude oil prices on the stock index of the mining sector. The data used in this study is a monthly transaction during the period 2013-2017 obtained from the official website of Bank Indonesia and the Indonesia Stock Exchange. Data were analyzed using multiple linear regression. The results show that partially gold prices and crude oil prices affect the stock index of the mining sector. Meanwhile, the exchange rate does not affect the stock index. Variations in exchange rates, gold prices, and crude oil prices were able to describe 63.3% of the variation in the stock index of the mining sector.